Modelling the Joint Distribution of Income and Wealth - Markus Jäntti; Eva Sierminska; Philippe Van Kerm (Institute for the Study of Labor (IZA), 2015)
This paper considers a parametric model for the joint distribution of income and wealth. The model is used to analyze income and wealth inequality in five OECD countries using comparable household-level survey data. We focus on the dependence parameter between the two variables and study whether accounting for wealth and income jointly reveals a different pattern of social inequality than the traditional 'income only' approach. We find that cross-country variations in the dependence parameter effectively accounts only for a small fraction of cross-country differences in a bivariate measure of inequality. The index appears primarily driven by differences in inequality in the wealth distribution.
Keywords: C1; D31; J10; 330; income; wealth; inequality; copula; multivariate Gini